2012
DOI: 10.1501/ashd_0000000078
|View full text |Cite
|
Sign up to set email alerts
|

Zihinsel engelli çocuğa sahip annelerin stresle baş etme yöntemlerinin değerlendirilmesi

Abstract: ÖzetAraştırma, Zonguldak il merkezinde yaşayan zihinsel engelli çocuğa sahip annelerin stresle başa çıkma yöntemlerinin değerlendirilmesi amacıyla tanımlayıcı olarak yapılmıştır. Zonguldak il merkezinde bulunan üç rehabilitasyon merkezine devam etmekte olan 210 zihinsel engelli çocuğun annesi araştırmanın evrenini oluşturmuştur. Araştırma süresince 178 anneye ulaşılmıştır (%84.8). Veri toplama aracı olarak araştırmacılar tarafından hazırlanan sosyodemografik özellikleri ve zihinsel engelli çocuğa sahip olma il… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
1
7

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 2 publications
2
11
1
7
Order By: Relevance
“…And then, EÇEP that was developed in accordance with these problems was applied, and the effectiveness of the program on depression and hopelessness levels of parents was examined. During the first step of the study, parents were identified to have a wide range of problems that were same with the ones stated in related literature (Ayyıldız, Şener, Kulakçı & Veren, 2012;Bridge, 2005;Cocks, 2000;Özşenol et.al., 2003). Findings also showed that the problems of the parents were interrelated to each other.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…And then, EÇEP that was developed in accordance with these problems was applied, and the effectiveness of the program on depression and hopelessness levels of parents was examined. During the first step of the study, parents were identified to have a wide range of problems that were same with the ones stated in related literature (Ayyıldız, Şener, Kulakçı & Veren, 2012;Bridge, 2005;Cocks, 2000;Özşenol et.al., 2003). Findings also showed that the problems of the parents were interrelated to each other.…”
Section: Discussionmentioning
confidence: 88%
“…Some of these problems which were related to the education process of the child (Shanker, 1995), health needs (Maatta, Maatta, Tervo-Maatta, Taanila, Kaski & Livanainen, 2011;Spender, Stein, Dennis, Reilly, Percy & Cave , 2008;Uygur & diğ.,2013), and social prejudices (Ayyıldız, Şener, Kulakçı & Veren, 2012;Beckett, 2009;Zibricky, 2014) have been observed to threaten psychological heath of parents in the long term. Continuity of these problems brings depression and hopelessness as a part of their lives for the parents with children with disabilities.…”
Section: Introductionmentioning
confidence: 99%
“…25 Yapılan çalışmalarda, beslenme alışkanlığı ile BKİ arasında pozitif, akademik başarı arasında negatif anlamlı ilişkinin olduğu bildirilmiştir. 15,17,20,26 Çalışma sonuçlarımız da yapılan önceki çalışma sonuçları ile benzerlik göstermektedir.…”
Section: Araştirmanin öRneklem Ve Katilimcilarin öZelli̇kleri̇unclassified
“…Stres bireyin yaşam olayları karşısında zorlanması demektir. Başa çıkma ise zorlanmaya neden olan durumlara bireyin yanıt verme şekli olarak tanımlanmaktadır (Ayyıldız, Şener, Kulakçı ve Veren, 2012). Lazarus, ve Folkman'a göre (1984), başa çıkma yöntemleri problem odaklı ve duygu odaklı yöntemler olarak ikiye ayrılmaktadır.…”
Section: Introductionunclassified